Raportowanie wyników badań - nauczanie a praktyka - Perek-Białas, Jolanta (Presentation of Research Results - Teaching and Practice, 2009)
In the following paper, various graphical possibilities of presenting research results are shown. First, there are presented simple charts, however not independently but together on one graph (as i.e. scatterplots with histogram, or box-plots with histogram). Further, there are shown how - on the graph - "typical" results of logistic regression could be illustrated by only statistically significant Exp(B). The Graphical Programming Language (GPL) could be used in order to obtain different graphs. GPL could be used via available statistical packages (i.e. PASW 17) and so it gives possibilities of more interesting presentations and visualization of the results.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 75-84